Heart failure therapy in patients with advanced cancer receiving specialized palliative care (EMPATICC trial) - Anker, Markus; Mahabadi, Amir A; Totzeck, Matthias; Tewes, Mitra; Khan, Muhammad Shahzeb; Mincu, Raluca I; Hendgen-Cotta, Ulrike B; Michel, Lars; Mathew, Baicy; Drescher, Ophelia; Schuler, Martin; Keller, Ulrich; et al. (European heart journal, 2025)
Advanced cancer may resemble a heart failure (HF)-like phenotype marked by cardiac wasting, dyspnoea, congestion, and/or physical dysfunction. The trial evaluated safety and efficacy of HF therapy among patients with advanced cancer receiving specialized palliative care to improve patients’ self-care ability.Patients with stage 4 solid tumours with a life expectancy of 1-6 months receiving specialized palliative care were enrolled. Patients were required to meet at least two cardiovascular risk criteria and at least one criterion for functional limitation. Participants were randomized 1:1 to receive optimized HF therapy (up to four drugs: sacubitril/valsartan, empagliflozin, ivabradine, ferric carboxymaltose) or placebo in a double-blind setting. The primary hierarchical endpoint included: (i) days alive and able to wash oneself, (ii) ability to walk 4 m, and (iii) self-reported patient global assessment (PGA) of subjective well-being, during the 30-day placebo-controlled phase.In five centres, 93 patients were randomized. The primary endpoint did not differ between groups (win ratio 0.95, 95% confidence interval [CI] 0.57-1.58; P = .83). Overall, mortality was 32% at 30 days (not different between groups). In patients alive at 30 days, HF therapy reduced N-terminal pro-B-type natriuretic peptide levels by 41% (P = .040), increased left ventricular ejection fraction by 2.9% (P = .036), and improved PGA scores (odds ratio 0.22, 95% CI 0.06-0.75; P = .016).In a population with advanced cancer receiving specialized palliative care and high early mortality, optimized HF therapy did not improve patients’ self-care ability. Among survivors at 30 days, improvements in quality of life measures and cardiac biomarkers suggest potential benefit of individualized HF therapy, which is hypothesis generating and needs validation.